The Effect of Ratio of Formaldehyde/Urea (F/U) using Catalyst of NaOH and NH4OH against Production of Urea-Formaldehyde Resin in Laboratory-Scale - Syaichurrozi, Iqbal (Eksergi, 2016)
This study was conducted to investigate the ratio of formaldehyde/urea (F/U) and catalysts against the formation of urea-formaldehyde resin. The F/U was varied in 1.5, 2, 2.5, 3. The catalysts used were NaOH and NH4OH. The results showed that density of urea-formaldehyde resin at F/U of 1.5, 2, 2.5, 3 was 1360, 1370, 1360, 1330 kg/m3 in using catalyst of NaOH and1370, 1370, 1350, 1350 kg/m3 in using catalyst of NH4OH. Meanwhile, the absolute viscosity of urea-formaldehyde resin at F/U of 1.5, 2, 2.5, 3 was 0.007347672; 0.007723512; 0.007347672; 0.006873174kg/m.s in using catalyst of NaOH dan 0.00879; 0.00827; 0.00813; 0.00643 kg/m.s in using catalyst of menggunakan NH4OH. Resin formed (%)at F/U of 1.5, 2, 2.5, 3 was 25.92; 30.19; 28.85; 25 % in using catayst of NH4OH dan 10.71; 11.6; 9.45; 14.28Â  % in using catalyst of NaOH.